2001
DOI: 10.1292/jvms.63.99
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Reproductive Performance in Pregnant, IL-2 Receptor .BETA.-chain Overexpressed Transgenic Mice.

Abstract: ABSTRACT. Relationships between female reproductive performance and uterine natural killer (uNK) cells were investigated in pregnant IL-2 receptor β-chain overexpressed transgenic (Tg2Rβ) mice. At 8 days of pregnancy, all fetuses were alive, suggesting that implantation normally occurred in these mice. However, 47% of fetuses were dead at 10 days of pregnancy and at 12 days all fetuses were resorbing, indicating that fetal loss progressed with the advance of pregnancy. The placenta of Tg2Rβ mice gradually decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Contradictory results have been reported about the relation between resistance to Heligmosomoides polygyrus and intestinal mastocytosis [1, 2, 5], and the specific effector mechanisms mediating worm expulsion remain unknown [1,15]. In the present study, we investigated the protective ability against H. polygyrus of Tg2R mice, in which mast cells are increased without inflammation.To obtain Tg2R mice, male Tg2R and female C57BL/ 6J (B6) were mated, and each offspring was verified to be a transgenic mouse by a PCR method, as described previously [10,14]. Transgenic and wild-type litter mate mice were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory results have been reported about the relation between resistance to Heligmosomoides polygyrus and intestinal mastocytosis [1, 2, 5], and the specific effector mechanisms mediating worm expulsion remain unknown [1,15]. In the present study, we investigated the protective ability against H. polygyrus of Tg2R mice, in which mast cells are increased without inflammation.To obtain Tg2R mice, male Tg2R and female C57BL/ 6J (B6) were mated, and each offspring was verified to be a transgenic mouse by a PCR method, as described previously [10,14]. Transgenic and wild-type litter mate mice were used.…”
mentioning
confidence: 99%
“…To obtain Tg2R mice, male Tg2R and female C57BL/ 6J (B6) were mated, and each offspring was verified to be a transgenic mouse by a PCR method, as described previously [10,14]. Transgenic and wild-type litter mate mice were used.…”
mentioning
confidence: 99%
“…Thus, diabetes may affect Fas/Fas-L system during pregnancy, so that uNK cells in the pregnant diabetes mice could persist on D18 of pregnancy. Similarly, since the decidual cells are also known to undergo apoptosis through Fas/Fas-L system during late pregnancy [5,19], it is likely that the decidua basalis in the pregnant diabetes mice could have larger area on D18 of pregnancy.…”
mentioning
confidence: 99%
“…Abnormally abundant uNK cells may compensate for the lack of PlGF secreted by trophoblast. Indeed, it is reported that uNK cells in IL-2 receptor -chain overexpressed transgenic mice (Tg2R) [19] and in IGF-I overexpressed mice [18] could alter in quality and behavior due to unusual condition. Similar changes or alterations on uNK cells may occur under diabetes condition.…”
mentioning
confidence: 99%
“…We have previously reported that uterine NK cells, which originally differentiate in the mouse pregnant uterus and contribute to pregnancy success, have morphological and differentiation irregularity in the Tg2Rβ placenta as compared with normal mice [2,3]. Furthermore, our primitive study found that the fertility rate and number of offsprings in Tg2Rβ females are very low (28.6% and 3.50 ± 3.54, respectively, n=7) as compared with wildtype females (100% and 6.71 ± 2.21, n=7), when they are paired with Tg2Rβ males.…”
mentioning
confidence: 99%